Pendampingan Penerapan Manajemen dan Adminstrasi Kaizen di Laboratorium IPA Sekolah TCS - Hafidz Hanafiah; Fransiska Tri Hapsari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Kaizen appears when many items are purchased but there is no or lack of control in their implementation. The purpose of this assistance activity in implementing Kaizen management and administration is to manage a science laboratory organization in a school so that the management of goods and administration can run well. The method used is the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) and PDCA (Plan, Do, Check, and Action). As a result of this activity, the TCS Science Laboratory can implement Kaizen well and can do it routinely and continuously.